RANCANG BANGUN WEBSITE PROGRAM STUDI DESAIN INTERIOR UNIVERSITAS SAHID SURAKARTA - Vinsensius Sony Role; Dwi Retnoningsih; Dahlan Susilo (JURNAL GAUNG INFORMATIKA, 2016)
Interior Design Study Program is one of the study program which is owned by private colleges Sahid University of Surakarta, which is located at Jln. Adi Sucipto No. 154, Surakarta Jajar Information owned by the Interior Design still shaped is a Company Profile. The information displayed is still very limited. Thus, the Interior Design Program at the University of Surakarta Sahid need a website to provide informations about courses. This study focuses on the delivery of information - information courses that complete, efficient and effective, the software used in building these applications are PHP (Hypertext Prepocessor) using framework Codeigniterl (CI) as a programming language, MySQL as the database server, Macromedia Dreamweaver and Notepad++ as a supporter. Research website Study Program Interior Design is tested using the method WebQual and got results 30 items questionnaire and have positive results between usability (Usability) website by visitors with a value of 0.080 and had a positive result between information (Infoqual) website by visitors with a value of 0.271 and also has a positive result of the interactions (Interactionsqual) website to visitors by showing the value of 0648.